Влияние прочностных и геометрических характеристик порошков синтетического алмаза на работоспособность бурового инструмента - Новиков, Н.В.; Богатырева, Г.П.; Ильницкая, Г.Д.; Богданов, Р.К.; Исонкин, А.М.; Закора, А.П.; Сирота, Ю.В.; Супрун, М.В. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The results of influence characteristics of strength and linear sizes on an overall performance
of the drilling tools are considered in this report. Application in the drilling tools of powders
of diamond homogeneous by strength and linear sizes allow increasing efficiency of the drilling
tool.